(3GdaJGhi GdeajOI hGdCLhHI GdSOjOIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hBdg hUMHg CLeYjf SFd GdTjN GdEeGe GdSHci eG Jbhd GdSGOI GdabgGA ai QLd MHS CeGcf hLYd GdfXQ ajgG ef HYOg dGHfJg dUdHg s
(3BNQgG (B:s
(3JfJgi HeSFdI hQOJ Ydi GdTjN ef OejGW SfI (B732 s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs